Optimizing the Potential of 3D Printing for Industry from Prototype to Production - Mohamad Agus Setiawan; Ageng Setiani Rafika; Ramzi Zainum Ikhsan; Ninda Lutfiani; Richard Evans (ADI Publisher, 2025)
The adoption of 3D printing technology has increased across various industrial sectors due to its ability to accelerate product development, reduce production costs, and support flexible manufacturing. However, implementation at the community and small–medium industry level remains limited due to gaps in technical skills, digital design knowledge, and structured technology transfer. This community service program aims to enhance the practical capacity of industrial partners in utilizing 3D printing, particularly in transitioning from prototyping to small-scale production. The program used the Participatory Action Research (PAR) approach through needs assessment, technology transfer training, hands-on practice, mentoring, and evaluation. Participants were guided in 3D modeling, printer setup, material selection, and print optimization. The program improved participants technical skills and confidence in producing functional prototypes according to industrial needs. Production time was reduced, design modification became more efficient, and opportunities for product innovation increased, supporting independent and adaptive manufacturing. This program successfully strengthened community-based industrial capabilities in adopting digital manufacturing, contributing to SDG 8 (Decent Work and Economic Growth) and SDG 9 (Industry, Innovation, and Infrastructure). Future activities are recommended to expand collaborative product development and sustain innovation networks between academia and industry.